Role of echocardiography in the management of veno-arterial extra-corporeal membrane oxygenation patients - Bailleul, Clotilde; Aissaoui, Nadia (Journal of Emergency and Critical Care Medicine, 2019)
Veno-arterial extracorporeal membrane oxygenation (VA ECMO) is a therapeutic option for patients with refractory cardiogenic shock (CS). It may also be used in other indications. Echocardiography remains the paramount bedside exam. In front of a refractory CS, an echocardiography should be run in order to get a good comprehension of the CS etiology and to settle the indication of ECMO (recovery expectation, contraindications such as aortic insufficiency…). At the implantation, echocardiography is the easiest way to control cannula position. After ECMO implantation, daily echocardiography helps understanding loading conditions, diagnosing complications and recovery. After several days of cardiopulmonary assistance, echocardiography guides the weaning strategy according to ECMO flow or helps deciding whether a new strategy is needed. Echocardiography is an essential tool to manage VA ECMO patients.